Cover Image. Issue 8 (24th August 2018) - Glover, Chris D.; Fernandez, Allison M.; Huang, Henry; Derderian, Christopher; Binstock, Wendy; Reid, Russell; Dalesio, Nicholas M.; Zhong, John; Stricker, Paul A.; ,
Abstract : The cover image, by Chris D. Glover et al., is based on the Research Report Perioperative outcomes and management in midface advancement surgery: a multicenter observational descriptive study from the Pediatric Craniofacial Collaborative Group, DOI:10.1111/pan.13418 .